Lafaz Musytarak dalam Diskursus Ushul Fikih: Analisis Semantik dan Konsekuensinya terhadap Penentuan Hukum - Miftahul Jannah; Nurul Islamiah; Abd Rauf Muhammad Amin; Zaenal Abidin (Kartika: Jurnal Studi Keislaman, 2026)
Musytarak (polysemous) expressions are terms that possess two or more distinct meanings, with each meaning having an equal possibility of being intended. This characteristic presents a unique challenge for Islamic scholars in interpreting the texts of Islamic law. The significance of studying lafaz musytarak has become increasingly important with the emergence of various new issues that are not explicitly addressed in the primary legal texts (nass). Through ijtihad that remains grounded in the principles of uṣūl al-fiqh, a comprehensive understanding of the concept, principles, consequences, and application of lafaz musytarak is therefore essential. This study employs a library research method. The findings reveal that lafaz musytarak refers to a term established to denote two or more meanings, with several indicators available for determining the preferred meaning (tarjīḥ), namely the context of the discourse (siyāq al-kalām), other relevant textual evidence (al-nuṣūṣ al-ukhrā), the prevailing linguistic convention (al-'urf al-lughawī al-ghālib), contextual circumstances (dalālah al-ḥāl), scholarly consensus (ijmāʿ) or the practices of the Companions, and the objectives of Islamic law (maqāṣid al-sharīʿah). The principles governing lafaz musytarak are established to prevent errors in the derivation of legal rulings (istinbāṭ al-aḥkām). Consequently, lafaz musytarak contributes to differences of opinion among scholars, serves as one of the methods of legal reasoning, and demonstrates the flexibility of Islamic law. In its practical application, lafaz musytarak plays a crucial role in addressing contemporary legal and social issues